The relationship between money supply (M2), gross domestic product (GDP), and inflation rate towards stock price of Kuala Lumpur industrial product index / Rosnani Ab. Talib - Ab. Talib, Rosnani (Faculty of Business and Management, 2006)
This project paper is to identify the relationship between Money Supply (M2), Gross Domestic Product (GDP), and Inflation Rate towards stock price of Kuala Lumpur Industrial Product Index .This project paper is also to determine which of the economic indicators (Money Supply-M2, Gross Domestic Product, and Inflation Rate) that are significant towards stock price of Kuala Lumpur Industrial Product Index. These three variables are parts of economic indicators always used by the researcher to identify the relationship of stock price performance reflected by the level of economy activities. The dependent variable is the Kuala Lumpur Industrial Product Index (IPI) and the independent variables consist of Money Supply (M2), Gross Domestic Product (GDP), and Inflation Rate. The study focuses on the economic indicators that have been recorded 6 years from January 1998 until December 2003 toward the Kuala Lumpur Industrial Product Index in the Main Board of Bursa Malaysia. This research uses the Multiple Linear Regression Analysis and Correlation Analysis in finding out the significant relationship between dependent variable and independent variables. From the finding, it has been concluded that Money Supply (M2) has no significant relationship, Gross Domestic Product (GDP) has significant relationship, and Inflation Rate has no significant relationship towards Kuala Lumpur Industrial Product Index (IPI).